The social mind classroom in transcomplex decolonial math education - Rodríguez, Milagros Elena (Revista Hipótese, 2022)
From a critical transdisciplinary transmethodology, the social mind classroom is analyzed in Transcomplex Decolonial Mathematical Education. As conclusions of openings, the social mind classroom in mathematics collaborates by demystifying elitist mathematics. Considerations of the human being, which means to educate is key in the relinking of teaching to become the social mind classroom, an educational emerging of application in varied contexts. New plateaus are re-linked, rhizomes in teachers, in which learning is no longer the ultimate end of the process without a relinked intermediate point, at all times students learn, unlearn and relearn.
Keywords: Classroom social mind; Mathematics education; Decolonial; Transcomplex; Religada